Transparansi Pengelolaan Dana Desa oleh Aparatur Desa dalam Perspektif Good Governance: Studi pada Desa Sidodadi, Kecamatan Lampung Timur - Navid Fajriant; Jidan Nuramadan; Choirul Salim; Icha Oktafia Khaerani (Tapis: Jurnal Penelitian Ilmiah, 2025)
This qualitative case study analyzes the practices and factors that influence the transparency of the management of the Sidodadi Village Fund. Data was collected through semi-structured interviews, observations, and analysis of budget documents (APBDes, RKPDes, LPJDes, LRA). The results show that transparency is implemented through formal mechanisms such as village meetings and bulletin boards, as well as informal channels such as social gatherings of village officials and communication at the sub-district level to reach hamlets. The findings identify factors that hinder effectiveness, namely regulatory restrictions on cost details, limitations in technology and human resources of the village apparatus, and variations in the information literacy of the community. This study concludes that although an information disclosure framework exists, residents’ substantive understanding of budget allocation remains limited. The empirical contribution of this research is the mapping of the role of informal channels in supporting transparency when digital means are not yet optimal, as well as the identification of regulatory restrictions that limit the depth of budget information disclosed. Furthermore, this study describes the interaction between formal procedures and social communication networks that shape access to information in rural environments. These findings form the basis for the development of adaptive and inclusive transparency strategies for rural contexts with varying levels of technological capacity and public literacy.